Wasting, Stunting, and Anemia in Angolan Children after Deworming with Albendazole or a Test-and-Treat Approach for Intestinal Parasites - Gasparinho, Carolina (2022)
Funding Information: Funding: This work was supported by the promoters of CISA (Camões, Institute of Cooperation and Language, Portugal; Calouste Gulbenkian Foundation (FCG); Government of Bengo Province; Angolan Ministry of Health—MINSA) and the National Malaria Control Program, Angola; the Foundation for Science and Technology (FCT, grants reference SFRH/BD/91566/2012, UIDB/00006/2020, UIDP/00006/2020, and UID/04413/2020); and the FCG (grant number 212008), Lisbon, Portugal. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.